Nanodermatology‐based solutions for psoriasis: State‐of‐the art and future prospects. Issue 6 (21st October 2019) - Damiani, Giovanni; Pacifico, Alessia; Linder, Dennis M.; Pigatto, Paolo D.M.; Conic, Rosalynn; Grada, Ayman; Bragazzi, Nicola L.
Abstract: Nanodermatology is an emerging, multidisciplinary science, arising from the convergence of nanotechnology, pharmacology, physics/biophysics, chemistry/biochemistry, chemical engineering, material science, and clinical medicine. Nanodermatology deals with (a) skin biology, anatomy, and physiology at the nanoscale (" skin nanobiology "), (b) diagnosis performed by means of novel diagnostic devices, assisted by nanobiotechnologies (" nanodiagnosis "), and (c) treatment through innovative therapeutic agents, including phototherapy (" photonanotherapy "/" photonanodermatology ") and systemic/topical drug administration (" nanotherapy ") at the nanoscale, and drug delivery—such as transdermal or dermal drug delivery (TDDD/DDD)—enhanced and improved by nanostructures and nanodrugs (" nanodrug delivery "). Nanodermatology, as a super‐specialized branch of dermatology, is a quite recent specialty: the "Nanodermatology Society" founded by the eminent dermatologist Dr. Adnan Nasir, was established in 2010, with the aim of bringing together different stakeholders, including dermatologists, nanotechnology scientists, policy‐makers and regulators, as well as students and medical residents. Psoriasis has a prevalence of 2–3% worldwide and imposes a severe clinical and societal burden. Nanodermatology‐based solutions appear promising for the proper treatment and management of psoriasis, assisting and enhancing different steps of the process of health‐care delivery: from the diagnosis to the therapeutics, paving the way for a personalized approach, based on the specific dysregulated biomarkers.